STUDENTS' CRITICAL THINKING SKILLS BASED ON GENDER IN BIOLOGY LEARNING ON ENVIRONMENTAL CHANGE MATERIAL IN CLASS X SMA NEGERI 4 PEKANBARU - Arihna, Mahirah; Suryanti , Suryanti (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to determine the Critical Thinking Ability of Students Based on Gender in Biology Learning on Environmental Change Materials in Class X of SMAN 4 Pekanbaru. This research is a qualitative descriptive research. The method used in this study is the survey method. Data collection was carried out using tests in the form of questions, initial observation sheets, interviews, and documentation. The sample in this study was 156 students. The results of the study showed that the overall average percentage of values obtained in the male gender was 67.80% in the medium category, and the female gender for the overall average score was 74.21% in the high category. It can be concluded that the ability to think critically on the gender of men and women in class X of SMAN 4 Pekanbaru has different categories.